The essential book of useless information the most unimportant things you'll never need to know - Voorhees, Don, Author (New York Perigee, 2009)
The newest entry in the #1 "New York Times"-bestselling Useless Information series offers a cornucopia of amazingly pointless facts and figures that will have trivia buffs marveling at all the things they never needed to know.
Keywords: Curiosities and wonders